First Examples of de Vries‐like Smectic A to Smectic C Phase Transitions in Ionic Liquid Crystals. Issue 24 (28th October 2016) - Kapernaum, Nadia; Müller, Carsten; Moors, Svenja; Schlick, M. Christian; Wuckert, Eugen; Laschat, Sabine; Giesselmann, Frank
Abstract: In ionic liquid crystals, the orthogonal smectic A phase is the most common phase whereas the tilted smectic C phase is rather rare. We present a new study with five novel ionic liquid crystals exhibiting both a smectic A as well as the rare smectic C phase. Two of them have a phenylpyrimidine core whereas the other three are imidazolium azobenzenes. Their phase sequences and tilt angles were studied by polarizing microscopy and their temperature‐dependent layer spacing as well as their translational and orientational order parameters were studied by X‐ray diffraction. The X‐ray tilt angles derived from X‐ray studies of the layer contraction and the optically measured tilt angles of the five ionic liquid crystals were compared to obtain their de Vries character. Four of our five mesogens turned out to show de Vries‐like behavior with a layer shrinkage that is far less than that expected for conventional materials. These materials can thus be considered as the first de Vries‐type materials among ionic liquid crystals. Abstract : Ionic de Vries liquid crystals : Five novel ionic liquid crystals with a smectic C phase, a common liquid crystal phase that is rarely found in ionic materials, are presented. Investigations into the phase transition from the orthogonal smectic A to the tilted smectic C phase reveal similarities to the tilting transition in "de Vries"‐type smectics.